Venezuelan International Meteorological and Hydrological Experiment (VIMHEX): hydrology report. v. 3, Geometric and hydraulic properties of the rivers - Simons, Daryl B., author; Richardson, E. V. (Everett V.), 1924-, author; Stevens, M. A., author; Duke, J. H., author; Duke, V. C., author; Civil Engineering Department, Colorado State University, publisher (Colorado State University. Libraries, 1971)
VIMHEX is an intensive program of tropical meteorological and hydrological observations taken in northeast Venezuela during the summer of 1969 to support a study of tropical atmospheric physics and the resulting effect of rainfall. The objectives of the program are to express the meso-scale weather structure in terms of the synoptic-scale envelope and to formulate the ground response to the rainfall produced by tropical weather disturbances over relatively flat tropical topography. The Hydrology Report, Volume III, is a compilation of the data obtained and utilized to develop relations between the discharge and the geometric and hydraulic properties at the primary and secondary river gaging stations. The report includes drawings of the plans, profiles and cross sections of 13 river reaches. The drawings are prepared from the field survey notes. The river basin slopes, obtained from topographic maps, at all gaging stations are listed. A summary of the bed-material size characteristics at 30 locations in the study area is given. The relations between the measured discharge and the corresponding cross-sectional area, average flow velocity, top width, wetted perimeter, hydraulic radius, hydraulic depth, top width to hydraulic depth ratio, and Manning's n are presented for 11 primary gaging stations.
Geometric and hydraulic properties of the rivers
CER70-71DBS-EVR-MAS-JHD-VCD-50.
October 1971.
Keywords: Streamflow -- Venezuela; Groundwater -- Venezuela; Stream measurements -- Venezuela; Water quality -- Venezuela